Evaluation of State-Mandated Third Trimester Repeat HIV Testing in a Large Tertiary Care Center - Berhie, Saba H.; Tsai, Stacy; Miller, Emily S.; Garcia, Patricia M.; Yee, Lynn M. (American Journal of Perinatology, 2022)
Objective The Illinois Perinatal HIV Prevention Act was passed to ensure universal HIV testing once during pregnancy and was extended in 2018 to add third trimester repeat HIV screening. The objectives of this analysis were to describe uptake of, and patient factors associated with, third trimester repeat HIV testing at a high-volume birthing center.Study Design This is a retrospective cohort study of people who delivered at a single tertiary care hospital in Illinois during 2018. Women who delivered before 27 weeks, had an intrauterine fetal demise, a known diagnosis of HIV, or no HIV test during pregnancy were excluded. Repeat testing was defined as an HIV test at or after 27 weeks' gestation after an earlier negative HIV test during the same pregnancy. The primary outcome was the proportion of people who received repeat testing prior to delivery. Bivariable analyses were performed to identify patient characteristics associated with documentation of repeat HIV testing.Results Of 12,053 people eligible for inclusion, 3.4% (n = 414) presented without a documented third trimester repeat HIV test. The proportion of people with repeat testing improved from 80 to >99% in the first year. Patient factors were largely not associated with testing performance although multiparous people were more likely to have documented repeat testing.Conclusion Rapid implementation of third trimester repeat HIV testing was achieved without disparity. Patient factors were largely not associated with testing performance which reinforces the goal of a universal screen to test all people equitably and effectively without bias.Key Points
Keywords: health care disparities; maternal health; public health; implementation science